The effect of seeding method on the growth of zinc oxide nanorods - Idris, Muhammad Idzdihar; Zainol Abidin, Yasmin; Mohd Yusof, Haziezol Helmi; Mohammed Napiah, Zul Atfyi Fauzan; Mohd Marzaini, Mohd Rashid; Zainudin, Muhammad Noorazlan Shah; Zainuddin, Hidayat (Universiti Malaysia Perlis, 2023)
The paper presents the investigation of the method of seeding process for the growth of zinc oxide (ZnO) nanorods (NRs) on the glass substrate as an electron transport layer (ETL) for solar cells. The ZnO NRs were grown by using the hydrothermal method. The seeding process was done via average deposition of zinc crystallite on the glass surface, and the process was compared between with and without spin coating technique. The effect of spin coating parameters during seeding phase on the growth of ZnO nanorods was also investigated in this study. It was found that the sample prepared using the unfiltered solution without spin coating in the seeding phase exhibited the densest ZnO NRs layer with the highest absorption coefficient and high crystallinity